Reception of Hryhoriy Tiutiunnyk`s creativity by literary critics - Головко, Людмила Григорівна; Федорова, Таїсія Євгенівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
This article explores the XX―XXI centuries scientific critical investigations devoted to the study of the Ukrainian writer`s Hryhoriy Tiutiunnyk creativity. Researchers of the 1960-1980s (P. Havrilov, Yu. Barabash, L. Volovets, etc.) keep focus primarily on revealing the relationship between the personality of the writer as a Soviet patriot and his work, as well as an analysis of such types of person represented by the writer as a Soviet man, a peasant man, a man-leader, a man-warrior and patriot-one, etc. Notwithstanding the prominent ideology of this period literary exploration, a number of important aspects related to the author`s style, problem content of works, peculiarity of the ideological and aesthetic evolution of the writer, originality of the artistic reproduction of the author’s concept were analyzed. Most scholars focus on the analysis of the novel “Vir”. M. Lohvinenko, K. Volynsky, B. Chip, L. Volovets, I. Semenchuk, Y. Barabash draw attention to the lyricism of the narrative in the novel and to the peculiarities of scenery images as a way of revealing character`s inner world. L. Volovets P. Havrilov, I. Semenchuk emphasize the psychological representation of characters images of the novel. Y. Badzo, L. Volovets, K. Volynsky and P. Serdyuk distinguish the motive of finding the truth in the writer`s works. The aforementioned researchers place emphasis on the analysis of war factor as a mean of revealing characters` personalities in the novel “Vir”. M. Lohvynenko, K. Volinskyi, B. Chip, L. Volovets, S. Lisovska, I. Semenchuk, Y. Barabash draw attention to the narrative lyricism of author`s work. L. Volovets, P. Gavrilov, I. Semenchuk emphasize the psychological nature of character image in the novel. Recently, S. Lisovsky’s works on poetry of his works have appeared. As well as O. Nezhyvyi, who outlines the history of novel publication and carry out a textual analysis of the first print, the modern version and the main text. It is proved that a comprehensive study of Hryhoriy Tiutiunnyk`s work of has not been accomplished yet.